Environmental Law Enforcement in Waste Management Based on Good Environmental Governance Principles in Denpasar City - I Dewa Gede Astika Praja Negara; Ni Made Jaya Senastri (Jurnal Hukum Prasada, 2024)
Waste management is still an unresolved problem. This study aims to examine problems in waste management in the city of Denpasar. This research is empirical legal research with a statutory approach. Data was collected with primary and secondary data and then analyzed qualitatively. Several laws and regulations correlate with waste management in Indonesia, namely Law No. 18 of 2008 concerning Waste Protection and Management. Structure, substance, and culture are three legal systems combined to make up law enforcement in the waste management industry. Moreover, there are two perspectives on law enforcement in waste management: preventive law enforcement and repressive law enforcement. To increase public awareness of a good and healthy environment, law enforcement in waste management also embraces the principles of Good Environmental Governance of the federal and municipal governments. The study results show that the Denpasar City Government already has mentoring rules regarding waste management. However, waste management based on good environmental governance in Denpasar City has not been effective. This is because the community and the lack of public awareness of healthy living still commit many violations. Thus, the government still needs to improve and increase the regulation and supervision of waste management in Denpasar City.